INFLUENCE OF LIGNIN PREPARATIOON ON CROPS DRY RESISTANT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
Basing on model experiments it was found, that lignosilicon compounds (LSi), synthesized in the Institute of the Wood Chemistry on the basis hydrolysis lignin, which has been used as fertilizer and growth activator for the cereals in the microfield and field environments, help plants to adapt for the soil water deficiency. Increase of drought resistance is explained by the plants ability to form the powerful root system on the background of the lignosilicon compound, which provides them with better water supply and nutrition. The weight of aboveground part of oats and wheat after the 15-day water stress experiment exceeded control values for up to 32% and 10% correspondingly. Due to LSi addition aboveground part of oats had better water retention, lesser water deficiency and transpiration intensity. Oats had shown better water retention comparing to control values, wheat - on the same level, as control. In total on the background of LSi wheat and oats revealed higher drought resistance than in the case of lignin application. The most antistress effects were observed for oats.